Threshold Reaction of Soil Arthropods to Simulative Nitrogen Deposition in Urban Green Spaces - Mo, Lingzi; Xu, Guoliang; Zhang, Jiaen; Wu, Zhifeng; Yu, Shiqin; Chen, Xiaohua; Peng, Bin; Squartini, Andrea; Zanella, Augusto (Frontiers in Ecology and Evolution, 2021)
Sustained Nitrogen (N) deposition has a wide-ranging impact on terrestrial ecosystems. However, we still paid little attention to urban soil fauna that responds to changes in N deposition. To clarify such effects on the soil properties and soil fauna in typical urban lawns (Cynodon dactylon), a control experiment was conducted for one year, in which NH4NO3 was added as the external nitrogen sources with four treatments of nitrogen addition N0 (i.e., only water), N1 (50 kg N ha−1 yr−1), N2 (100 kg N ha−1 yr−1), N3 (150 kg N ha−1 yr−1). Results show that N deposition additions influence soil faunal communities in soil of urban lawns. The relative abundance of Oribatida increased with the N treatment level, partially replacing the more sensitive Collembola. Significant differences in the Shannon-Wiener and Margalef indices (p < 0.01) supported this statement. Although higher doses of N deposition showed adverse effects on soil fauna communities, low nitrogen depositions increased the soil fauna diversity and richness, especially at 5-10 cm depth. A threshold effect appears to exist in this sense: low nitrogen deposition (< 25 kg N ha-1 yr-1) did not affect negatively pedofauna structure and composition, while in the range from these values up to 50 kg N ha-1 yr-1, the composition of the pedofauna underwent major changes confirmed by the fall of biodiversity indices. These changes are accompanied by a drop in pH values ensuing the increasing nitrogen inputs.